Organisational transformation of Bank Islam Malaysia Berhad - Abdel Karim, Abdel Aziz Adam (1998)
This study was to identify the organisational transformation of BIMB since its establishment in 1983. It also identified the elements that contribute positively or negatively towards this change and the intervention techniques being practiced. The sources of data were in-depth interviews with three BIMB management officers (human resource manager, marketing manager and retail banking manager) in the Head Office in Kuala Lumpur and a field survey covered 15 randomly selected branches in KL and Selangor State. A sample of 122 BIMB staff members filled in the questionnaire in this survey. BIMB documents were also employed as a secondary source. The in-depth interviews concerned about the organisational transformation of BIMB, external elements motivate to change, intervention techniques being practised and organisation resistance to change Staff questionnaire was close-ended aimed at identifying staff resistance to change BIMB documents were employed to support the interviews The data analysis included descriptive statistics in terms of mean and frequency counts, categoristation of interviews, and a content analysis of documents were used to answer the objectives The findings of this study revealed that BIMB has experienced different intervention techniques to cope with the changing environment in terms of liquidity, market competition, macroeconomics trends and crisis, technological innovation and globalisation and liberalisation As a result of its transformation, BIMB witnessed a great development and change, in terms of capital, size and functions. Also the results showed that BIMB capabilities in terms of capital and infrastructure support any change plans In contrast, the study showed that staff resist change because it threats their social environment, old routine and values.